The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1136/bmjopen-2017-019814
|View full text |Cite
|
Sign up to set email alerts
|

Self-management interventions for adults with chronic kidney disease: a scoping review

Abstract: ObjectiveTo systematically identify and describe self-management interventions for adult patients with chronic kidney disease (CKD).SettingCommunity-based.ParticipantsAdults with CKD stages 1–5 (not requiring kidney replacement therapy).InterventionsSelf-management strategies for adults with CKD.Primary and secondary outcome measuresUsing a scoping review, electronic databases and grey literature were searched in October 2016 to identify self-management interventions for adults with CKD stages 1–5 (not requiri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
106
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 95 publications
(118 citation statements)
references
References 63 publications
(30 reference statements)
6
106
0
6
Order By: Relevance
“…The results of our survey of Canadian CKD clinics are consistent with our scoping review of self-management interventions for adults with CKD, 13 with nurses being the most common provider and the outpatient setting the most common location. 13 There were a few differences also noted.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The results of our survey of Canadian CKD clinics are consistent with our scoping review of self-management interventions for adults with CKD, 13 with nurses being the most common provider and the outpatient setting the most common location. 13 There were a few differences also noted.…”
Section: Discussionsupporting
confidence: 81%
“…The results of our survey of Canadian CKD clinics are consistent with our scoping review of self-management interventions for adults with CKD, 13 with nurses being the most common provider and the outpatient setting the most common location. 13 There were a few differences also noted. While self-management interventions commonly reported in the literature are related to topics of diet and nutrition and delivered face-to-face, 13 modality education and print were the most common topics and delivery format reported by the CKD clinics in our survey.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…7 Five patient partners and 1 caregiver were engaged in the previous phases of this work, including a scoping review, a survey of chronic kidney disease clinics, analysis of behaviours of patients with chronic kidney disease and caregivers by means of the Theoretical Domains Framework and a qualitative study. 5,6,8,9 This has laid the foundation for the present study. Based on the qualitative study, 8 topic areas were identified -understanding chronic kidney disease, diet, medications, symptoms, finances, mental and physical health, travel and work/school -as well as features including mixed-content formats (e.g., visuals, text, user-generated content).…”
Section: Openmentioning
confidence: 90%
“…Research created a skeleton persona using quantitative and qualitative data from our prior work including demographic description (e.g., age, diagnosis, hobbies, life experiences), goals (e.g., lifestyle) and challenges (e.g., frustrations, concerns). 5,8 In consultation with our 6 patient partners, using an iterative process, we modified persona features, including names, goals, challenges, technical ability (computer literacy, Internet use/ availability) and health behaviour characteristics (health literacy, support networks, knowledge of health status, readiness for change). The revised personas were reviewed at an inperson research team meeting and were finalized through discussion and agreement.…”
Section: Persona Cocreationmentioning
confidence: 99%